Pyramidal ownership and the creation of new firms - Bena, Jan; Ortiz-Molina, Hernán (Journal of Financial Economics, 2013)
We study the role of pyramidal ownership structures in the creation of new firms. Our results suggest that pyramids arise because they provide a financing advantage in setting up new firms when the pledgeability of cash flows to outside financiers is limited. Parent companies supply inside funds to new firms that, due to large investment requirements and low pledgeable cash flows, cannot raise enough external financing. The financing advantage of pyramidal structures is pervasive in many countries, exists regardless of whether new firms are set up by business groups or by smaller organizations, and is an important underpinning of entrepreneurial activity.